FEEDBACK THAT AFFECTS FIRST YEAR MEDICAL STUDENT’S LEARNING IN HIGH POWER DISTANCE & COLLECTIVISM CULTURE - Ida Ayu Triastuti; Gandes Retno Rahayu; Yoyo Suhoyo (Faculty of Medicine Universitas Kristen Duta Wacana, 2019)
Background: Constructive feedback is an essential component of learning for medical undergraduate. Communication culture of high-power distance and collectivism might have influence in shaping students' perception of the benefit of feedback. Aim: This study is aimed to identify feedback characteristic which associated with students' perception of learning benefit, and further explored the mechanism feedback influence on students learning process. Method: This is a mixed method study, with explanatory sequential approach. The setting is first-year medical undergraduate students at FK UKDW who enrolled in skill lab class (pulmonary physical examination). The first phase is a quantitative study using questionnaire on feedback characteristics and student’s perception of feedback benefits, further analysed with linear regression methods. The next phase is an interview study on selected students with semi-structured questions, and further analysed with thematic analysis. Result: There are 82 students who returned the questionnaire. Quantitative analysis showed that feedback including comparison to standard (B=2,26; p = 0,003) and follow-up planning (B=3,47; p < 0,001) are associated with perceived benefit by students. Further interview of 11 students discovered that students have received clear and concise outline through the feedback process. On the other hand, the communication culture, poor execution of feedback process, and interconnectedness between each characteristic may influence the students' perception of benefits. Conclusion: Feedback is beneficial for medical undergraduate students in high power distance and collectivist culture, specifically feedback with comparison to standard and follow-up planning.